The Development of Indonesian Islamic Civilization During The Dutch Colonial Period - Robi'atul Adawiyyah, Vina; Eka Wati, Erlina; Nasikhin; Fihris (LPPM Institut Al Azhar Menganti Gresik, 2023)
This study aims to analyze the development of Indonesian Islamic civilization during the Dutch colonial period. This study using library research produces research data that: 1). The dynamics of the socio-cultural conditions of Islamic civilization during the Dutch colonial period were still underdeveloped due to the strict system of colonialism applied in Indonesia; 2). The government system of Islamic civilization during the Dutch colonial period greatly influenced the development of Islamic civilization in Indonesia; 3). There were 3 strategies for Islamic da'wah during the Dutch colonial period, including: the transitional da'wah system between Hinduism and Islam, the lecture method in surau, and Islamic boarding schools; 4). Challenges to Islamic civilization during the Dutch colonial period included: Challenges in the fields of education, politics, economy and religion or da'wah; 5). Influential figures during Islamic civilization during the Dutch colonial period included K.H. Hasyim Asy'ari, Prince Diponegoro, Tuanku Imam Bonjol, Prince Antasari, and Teungku Cik Di Tiro. This study has implications for increasing literature on the history of Indonesian Islamic civilization so that it can add to the treasury of historical knowledge in Indonesia.